Visualizing Literacy: Images, Media, and Method - Bonfiglio, Ryan P. (Biblical interpretation, 2017)
While biblical scholars have long been interested in questions about textual literacy in the ancient world, relatively little attention has been given to the concept of visual literacy – that is, the extent to which images were produced and read as a type of language. The following article introduces this concept as it has been developed in recent work in visual culture studies and then offers a series of probes that attempt to assess the prominence of visual literacy in the ancient Near Eastern world. Though it is not possible to arrive at a precise rate of visual literacy, there is ample evidence to suggest that those who produced/commissioned art were highly concerned about questions regarding the readability of their materials and often privileged artistic motifs over epigraphic content in the design and implementation of certain mixed-media artifacts. These lines of evidence suggest that images functioned as a prominent vehicle of communication in the ancient world alongside, and sometimes in place of, text-based media. Research on visual literacy not only sheds new light on the ancient media contexts of the biblical world but also offers a more explicit rationale for how and why ancient images should be used in biblical interpretation today.